What ails bank deposit mobilization and credit creation in Kenya? - Benjamin Maturu (Kenya Bankers Association (KBA), 2021)
We estimate a proposed core financial intermediation model built upon an extended classical quantity theory using Bayesian econometric techniques. The findings suggest that the persistent deceleration in bank deposits, bank credit and domestic final output during the most of the second half of the decade ending in Dec. 2019 is due to a downward spiral (or a vicious circle) of bank deposits, bank credit and domestic final output caused by a reversal of hitherto accommodative economic and financial policies meant to revitalise the economy following the 2007 post-election disturbances and to check adverse contagion effects from the global economic and financial crises. With accommodative economic and financial policies including relaxed compliance with provisioning for non-performing bank loans, the gross non-performing bank loans accumulated to unprecedented levels thereby adversely affecting effective demand for and supply of bank credit in the private sector. This situation was aggravated by tightening monetary policy stance using the central bank rate amid tighter requirements for compliance with provisioning for non-performing loans.
Keywords: 330; Einlagensicherung; Kreditgeschäft; Bankenregulierung; Kenia